Analysis of Error Using Simple Past Tense on Recount Text Class VIII B Students of SMP Pelita Ngabang in the Academic Year 2019/2020 Landak District - Nopinawati Tuminah; Yustina Selong; Noor Faridha (Udayana Journal of Social Sciences and Humanities, 2021)
This research aims at investigating the errors using simple past tense that is often done by students in the activity of writing sentences in simple past tense on the recount text of class VIII B of junior high school PELITA Ngabang in the academic year 2019/2020 Landak Regency. The study uses a qualitative research design. The research was carried out at junior high school PELITA Ngabang on November 22nd, 2019. The research subjects were VIII B amount of 20 students. After analyzing the errors of the 20 past forms in the recount text that were finished by 20 students there were 73 errors. Finally, the authors concluded that the past form errors in the recount text were the types of errors omissions, 19, 17%, type of errors addition 26, 02%, types of errors misformation 27, 39%, types of errors misordering 27, 39%.